2014
DOI: 10.1007/s11046-013-9726-0
|View full text |Cite
|
Sign up to set email alerts
|

Equine Pulmonary Aspergillosis with Encephalitic, Myocardial, and Renal Dissemination

Abstract: The cause of the death of a 16-month-old Brasileiro-de-Hipismo filly and a 3-year-old male Paint Horse with clinical manifestations of anemia and apathy from southern Brazil was investigated. These horses were maintained at the same stable; received hay as part of their diet and were submitted for routine necropsy evaluations. Significant gross findings included several nodules randomly distributed throughout the pulmonary lobes of both horses, and the kidneys, myocardium, and the frontal lobes of the cerebrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
2
5
0
1
Order By: Relevance
“…The intralesional fungal hyphae observed at the trachea, nasal cavity, rumen, and colon by routine histopathology and better visualized with the histochemical stain are consistent with previous descriptions of Aspergillosis -induced diseases in veterinary [ [31] , [32] , [33] , [34] , [35] ] and human [ [10] , [11] , [12] , 36 ] medicine. Moreover, speciation to A. fumigatus was confirmed due to morphological characteristics observed from the specimens subjected to mycological evaluation; similar morphologic findings were described [ [37] , [38] , [39] ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The intralesional fungal hyphae observed at the trachea, nasal cavity, rumen, and colon by routine histopathology and better visualized with the histochemical stain are consistent with previous descriptions of Aspergillosis -induced diseases in veterinary [ [31] , [32] , [33] , [34] , [35] ] and human [ [10] , [11] , [12] , 36 ] medicine. Moreover, speciation to A. fumigatus was confirmed due to morphological characteristics observed from the specimens subjected to mycological evaluation; similar morphologic findings were described [ [37] , [38] , [39] ].…”
Section: Discussionsupporting
confidence: 89%
“…Consequently, adequate mycological evaluation by experienced professionals can result in the diagnosis of A. fumigatus from tissues using classical mycology [ 41 ], without the need for molecular methods. Similar diagnostic strategies for aspergillosis were reported in horses [ 31 , 35 ]. Additionally, the intralesional identification of BVDV and MCFV antigens in multiple tissues and restricted identification of BoHV-1 antigens at the trachea demonstrated that this calf was infected by these viral pathogens, confirming four concomitant infections in this animal.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The high temperature environment during the maturation along with the relative humidity is a perfect habitat for thermotolerant organisms like A. fumigatus , which could finally lead to a contamination of the food stock and entry to the food chain. The fact that horse and poultry feed samples had the greatest contamination frequency (Pena et al ., ) might explain the infection of horses (Hilton et al ., ; Headley et al ., ) and turkey poults with A. fumigatus . The isolates from different tissues showed the ability to produce GT.…”
Section: Prevalence Of Gt In the Environment And Food Chainmentioning
confidence: 99%